1997
DOI: 10.1161/01.atv.17.11.3071
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Oral and Transdermal Estrogen/Progesterone Regimens on Blood Coagulation and Fibrinolysis in Postmenopausal Women

Abstract: Postmenopausal hormone replacement therapy is associated with a reduction in the incidence of coronary heart disease. However, inconclusive results have been reported with respect to the risk of stroke, and recent studies consistently showed an increased risk of venous thromboembolism in postmenopausal women using oral estrogen. There are surprisingly few interventional studies to assess the true effects of estrogen-progestin regimens on blood coagulation and fibrinolysis, and the impact of the route of estrog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

25
227
4
15

Year Published

2002
2002
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 337 publications
(271 citation statements)
references
References 52 publications
25
227
4
15
Order By: Relevance
“…Existem evidências de que os efeitos da terapia hormonal sobre o mecanismo de coagulação e fibrinólise dependem da via de administração oral ou não oral do estrogênio (24,33) e do tipo de progestágeno utilizado. Possíveis razões para esses achados seriam que a reposição estrogênica oral contribui para a síntese hepática de fibrinogênio e pode ocasionar um aumento significativo na capacidade fibrinolíti-ca global através da diminuição de t-PA e PAI-1 (10,34,35), mas também interfere na síntese dos anticoagulantes naturais como proteínas C, S e antitrombina (36,37). Com o estrogênio não oral esta primeira passagem não ocorre, não havendo tanta interferência na síntese hepática de proteínas.…”
Section: Estudounclassified
See 2 more Smart Citations
“…Existem evidências de que os efeitos da terapia hormonal sobre o mecanismo de coagulação e fibrinólise dependem da via de administração oral ou não oral do estrogênio (24,33) e do tipo de progestágeno utilizado. Possíveis razões para esses achados seriam que a reposição estrogênica oral contribui para a síntese hepática de fibrinogênio e pode ocasionar um aumento significativo na capacidade fibrinolíti-ca global através da diminuição de t-PA e PAI-1 (10,34,35), mas também interfere na síntese dos anticoagulantes naturais como proteínas C, S e antitrombina (36,37). Com o estrogênio não oral esta primeira passagem não ocorre, não havendo tanta interferência na síntese hepática de proteínas.…”
Section: Estudounclassified
“…A MDP de forma cíclica não pareceu afe-tar a diminuição de F induzida pelos estrogênios, porém de forma contínua sim, também diminuindo níveis de fator VII, um componente do TAP (18,21,24,25). Já a progesterona micronizada, como utilizada em nosso trabalho, de forma cíclica, foi descrita inibindo ou não a queda de F induzida pelos estrogênios (10,21,28). De forma geral, os efeitos sobre coagulação são mais favoráveis ao se utilizar estrogênio isolado, por via oral ou não.…”
Section: Estudounclassified
See 1 more Smart Citation
“…Nonetheless, a pilot study in type 2 diabetics (open, longitudinal follow-up study of 19 HRT users and nine controls) found that none of the measured markers of cardiovascular risk were adversely affected by transdermal HRT, contrasting with previous studies using oral preparations (Stojanovic et al, 2003). Other studies of venous thromboembolism risk have found that transdermal HRT was not associated with the procoagulant effects of the oral agents (Scarabin et al, 1997), and one case-control study reported that the venous thromboembolism risk associated with oral HRT was not found with transdermal formulations (Scarabin et al, 2003).…”
mentioning
confidence: 90%
“…Observational studies have suggested possible beneficial effects of HT, notably on coronary heart disease (CHD) mortality (see for metaanalysis 5 ), but the most recent randomized controlled trial (RCT) of the women's health initiative (WHI) study observed a significant increase in CHD risk related to estrogen plus progestogen therapy (EPT) only [6][7][8] . The inconsistency between studies has been attributed to differences in population, time from HT initiation 9 and HT formulation [10][11][12][13][14][15][16][17] . In the WHI, women were older than 65, less healthy, with vascular risk at randomization, and used conjugated equine estrogens (CEE) opposed or not with medroxyprogesterone acetate (MPA), which confers higher vascular risk than transdermal 17-estradiol and micronized progesterone, regarding a number of markers, such as blood coagulation, C Reactive Protein, or LDL-C particle size [12][13][14][15][16] .…”
Section: Introductionmentioning
confidence: 99%